Analysis of a molten carbonate fuel cell: cogeneration to produce electricity and cold water - Silveira, J. L.; Leal, E. M.; Ragonha, L. F. (Elsevier B.V., 2001)
The fuel cell is an emerging cogeneration technology that has been applied successfully in Japan, the USA and some countries in the European Union. This system performs direct conversion of the chemical energy of the oxidation of hydrogen from fuel with atmospheric oxygen into direct current electricity and waste heat via an electrochemical process relying on the use of different electrolytes (phosphoric acid, molten carbonate and solid oxide, depending on operating temperature). This technology permits the recovery of waste heat, available from 200 degreesC up to 1000 degreesC depending on the electrolyte technology, which can be used in the production of steam, hot or cold water, or hot or cold air, depending on the associated recuperation equipment. In this paper, an energy, exergy and economic analysis of a fuel cell cogeneration system (FCCS) is presented. The FCCS is applied in a segment of the tertiary sector to show that it is a feasible alternative for rational decentralized energy production under Brazilian conditions. The technoeconomic analysis shows a global efficiency or fuel utilization efficiency of 86%. Analysis shows that the exergy losses in the fuel cell unit and the absorption refrigeration system are significant. Furthermore, the payback period estimated is about 3 and 5 years for investments in fuel cells of 1000 and 1500 US$/kW, respectively. (C) 2001 Elsevier B.V. Ltd. All rights reserved.